Coordinates of Service Industry in European Union. A Marketing Perspective - Cristinel CONSTANTIN (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2017)
The economic convergence is one of the most important objectives of the European Union (EU). According to this objective the member states have to make efforts in order to reach the living standards of the most developed countries. This paper aimed at identifying the position of the Romanian economy among the other member states concerning the GDP per capita and the ratio of service sector in the Gross Added Value. The results reveal that there is a gap between the Romanian economy and the average of EU. This gap can be bridged by a smart and sustainable development of service industry, which is also situated below the values recorded in the developed countries. Such goals can be attained by proper strategies of service industry development that should be put in practice both by Romanian authorities and the decision makers inside the companies. All these strategies have also to consider the development of the other economic sectors because the service sector cannot sustain the economic growth only by itself.